1992
DOI: 10.1136/hrt.68.11.531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the recommendations of the British Pacing and Electrophysiology Group on pacemaker prescription and on the immediate costs of pacing in the Northern Region

Abstract: Background-The report from the Working Party of the British Pacing and Electrophysiology Group recommends the use of more sophisticated pacemakers in most patients. These proposals were initially circulated in - September-1990 Conclusions The adoption of the recommendations of the British Pacing and Electrophysiology group in the Northern Region would greatly increase the cost of pacing hardware. The greater part of this increase would be attributable to the routine use of dual chamber pacing in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 3 publications
0
11
0
2
Order By: Relevance
“…[47][48][49][50][51][52][53][54][55][56][57][58] One study 54 considered the cost-effectiveness of dual-chamber versus single-chamber atrial pacing, making it the most relevant non-UK economic evaluation. The remaining four studies considered the cost-effectiveness of dual-chamber versus single-chamber VP.…”
Section: Systematic Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…[47][48][49][50][51][52][53][54][55][56][57][58] One study 54 considered the cost-effectiveness of dual-chamber versus single-chamber atrial pacing, making it the most relevant non-UK economic evaluation. The remaining four studies considered the cost-effectiveness of dual-chamber versus single-chamber VP.…”
Section: Systematic Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
“…47,53 A narrative review of these studies is presented in the section Narrative summary of included non-UK economic evaluations, with quality assessment against the NICE reference case and Philips checklist 59 presented in Appendix 3, Quality assessment. The single UK-specific costing study 57 identified in the TAG's systematic review of the economic literature provides information on the cost of devices incurred by a single centre in 1991 and is therefore of limited use to inform an up-to-date economic evaluation.…”
Section: Systematic Review Of Existing Cost-effectiveness Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…2 However, considerable differences have been reported in the frequency of implantation of pacemakers and in the system selected. 3,4 Studies discussing the clinical profile of the patients undergoing pacemaker implantation are available in Western literature, there are not many studies from the India, in view of which we conducted a study to assess clinical profile of the patients undergoing pacemaker implantation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Relatively little is known about the reasons for these differences. 5 There is some evidence that patients' sex might play a part in clinical decision making. [6][7][8] We used a large database to analyse whether sex can explain differences in the selection of pacemaker systems.…”
Section: Introductionmentioning
confidence: 99%